Waspada Pola Asuh Otoriter Dapat Menyebabkan Anak Kurang Percaya Diri - Rhamadhan, Faiza (TSAQOFAH, 2026)
Authoritarian parenting is a parenting style characterized by numerous rules, high demands, and minimal two-way communication between parents and children, and it is still frequently found in family life, leading to negative effects on emotional and social development, particularly children’s self-confidence. This article aims to explain the concept of authoritarian parenting, analyze its impact on children’s self-confidence, and describe strategies that parents and teachers can implement to promote the use of more positive parenting styles, particularly in the context of nonformal education. The method used is a literature review based on various scholarly sources such as journals, books, and previous research relevant to parenting, self-confidence, and nonformal education. The findings show that authoritarian parenting significantly contributes to low levels of children’s self-confidence, as reflected in children’s tendency to fear making mistakes, difficulty in making decisions, and reluctance to try new things because they are accustomed to mere obedience without being given space to express their opinions. These findings underscore the need to shift towards positive parenting styles that are more democratic, communicative, and supportive, so that children can grow into confident, independent individuals who are able to express themselves in a healthy manner. This article contributes to enriching perspectives on family education and nonformal education by emphasizing the collaborative role of parents and educators in building a constructive parenting climate for the development of children’s self-confidence.